Adoção homoparental e infância: uma análise da mídia - Temperini, Carlos Augusto Teixeira (2012)
The aim of this study is describe and interpret subjects about homoparental adoption and childhood which could be found in Folha de S. Paulo online newspaper, published between the years of 2000 and 2011, to comprehend the social construction of childhood and debate about homoparental adoption. The study hypothesis is that the construction of social problems is subordinated by domination relationship. The theme publishment in the biggest Brazilian newspaper multiplies, through symbolic forms, relations of power. The theory structure of this study was built by ideology studies of John B. Thompson (2009) and social studies about childhood. To analyze the newspaper was used deep hermeneutic and content analysis of Bardin (1977). Elected as the universe of this study 245 newspaper articles between the years of 2000 and 2011, about homoparental adoption and childhood. To compose the corpus of this study was selected newspaper articles that show national content. At least, was selected 16 articles that portray cases of homoparental adoption. The results introduce the homoparental adoption theme being debated in the newspaper articles as a secondary theme, diluted in the new discussions of adoption law, such as the homosexual civil union. Observed, yet, that adoption is directly connected to the right of build a family the newspaper didn´t discussed this issue in the range of children´s rights either homosexual´s rights. The treatment given to the homoparental adoptions questions was much more polemized than discussed, obfuscating childrens and teenager s rights. Examinating the ethical principle, the speech by Folha de S. Paulo about homoparental adoption and childhood disregard the well-being of the characters presented, might be consider ideological once it contributes to stigmatization of children and homossexuals, supporting relations of domination